Heteronuclear Efimov scenario with positive intraspecies scattering length - Ulmanis, Juris; Häfner, Stephan; Pires, Rico; Kuhnle, Eva; Wang, Yujun; Greene, Chris H.; Weidemüller, Matthias (Physical review letters, 2016)
We investigate theoretically and experimentally the heteronuclear Efimov scenario for a three-body system that consists of two bosons and one distinguishable particle with positive intraspecies scattering lengths. The three-body parameter at the three-body scattering threshold and the scaling factor between consecutive Efimov resonances are found to be controlled by the scattering length between the two bosons, approximately independent of short-range physics. We observe two excited-state Efimov resonances in the three-body recombination spectra of an ultracold mixture of fermionic 6Li and bosonic 133Cs atoms close to a Li-Cs Feshbach resonance, where the Cs-Cs interaction is positive. Deviation of the obtained scaling factor of 4.0(3) from the universal prediction of 4.9 and the absence of the ground state Efimov resonance shed new light on the interpretation of the universality and the discrete scaling behavior of heteronuclear Efimov physics.
Gesehen am 29.05.2020